Prevalensi Buruh Kayu dengan Ketergantungan Nikotin di Denpasar Selatan - Bhagawanti, Ayu Gita; Arijana, I Gusti Kamasan Nyoman (E-Jurnal Medika Udayana; Vol 6 No 12 (2017): E-Jurnal Medika Udayana, 2017)
Cigarette consumption is still a major cause of preventable disease and premature death in the United States and other countries, including Indonesia. The purpose of this study was to determine the proportion of the nicotine-dependence among woodworkers in South Denpasar. The experiment was conducted in a number of wooden warehouses in South Denpasar on 19-26 November 2013. This is descriptive research with sample size 35 people using purposive random sampling. Data obtained by The Fagerstrom Test for Nicotine Dependence (FTND). The results showed those with nicotine-dependence as much as 29 samples (83%) are migrants, 6 samples (17%) were Balinese. For the level of education dominated by the High School/Vocational (SMA/K) by 12 samples (34%), Junior High School (SMP) as many as 11 samples (31%), elementary school (SD) by 8 samples (22%), Bachelor degree as much as 3 samples (8%), and those didn’t enter school as much as 1 sample (2%). On table 2, it appears that the prevalence of nicotine dependence is extremely high, with the number of 35 samples, 14 samples (40%) is very high, 9 of them (25%) were as classified high, 7 (20%) were classified as moderate, 5 (14%) were classified as low. There is no population classified as very low. Keyword: cigarette, nicotine, The Fagerstrom Test for Nicotine Dependence (FTND)